2015
DOI: 10.1111/acer.12670
|View full text |Cite
|
Sign up to set email alerts
|

Who Drinks Where: Youth Selection of Drinking Contexts

Abstract: Background Different drinkers may experience specific risks depending on where they consume alcohol. This longitudinal study examined drinking patterns, demographic and psychosocial characteristics associated with youth drinking in different contexts. Methods We used survey data from 665 past-year alcohol using youths (ages 13–16 at Wave 1) in 50 midsized California cities. Measures of drinking behaviors and drinking in seven contexts were obtained at three annual time points. Other characteristics included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
30
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 24 publications
7
30
1
2
Order By: Relevance
“…Although simultaneous use (i.e., use of more than one substance within a few hours) is common among young substance users (Pape et al, 2009; Schepis et al, 2016; Subbaraman and Kerr, 2015), we know very little about contexts and risks associated with simultaneous use of alcohol and marijuana. We know that risks for underage drinking vary from one context to another and that drinking contexts, independently of how much a person drinks, are related to specific problems (Bersamin et al, 2016; Lipperman-Kreda et al, 2015; Mair et al, 2015), but we do not know if contexts of simultaneous alcohol and marijuana use are unique or whether simultaneous use leads to greater problems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although simultaneous use (i.e., use of more than one substance within a few hours) is common among young substance users (Pape et al, 2009; Schepis et al, 2016; Subbaraman and Kerr, 2015), we know very little about contexts and risks associated with simultaneous use of alcohol and marijuana. We know that risks for underage drinking vary from one context to another and that drinking contexts, independently of how much a person drinks, are related to specific problems (Bersamin et al, 2016; Lipperman-Kreda et al, 2015; Mair et al, 2015), but we do not know if contexts of simultaneous alcohol and marijuana use are unique or whether simultaneous use leads to greater problems.…”
Section: Introductionmentioning
confidence: 99%
“…Substance use context is defined as the location, and situational and social characteristics of a specific substance use event (Freisthler et al, 2014). Limited research has found that situational (e.g., lack of adult supervision, alcohol availability, and lack of enforcement) and social (e.g., group size) context characteristics contribute to increased adolescent alcohol use (Bersamin et al, 2016; Grune et al, 2017; Jackson et al, 2016; Lipperman-Kreda et al, 2015). Characteristics of drinking or substance use contexts may influence alcohol or substance use and problems through increased access and opportunities to engage in risky behaviors (Flewelling et al, 2013; Ryan et al, 2010) or through social modeling, social pressure, or social norms (Chan et al, 2017; Handren et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Each drinking event occurs within a setting of specific circumstances, including social factors, such as the attributes of others in attendance; situational factors, such as alcohol availability and adult supervision; and the location of the event itself (Freisthler et al., ). Risk for underage alcohol use and consequences varies across these factors, and drinking contexts are associated with the risk of experiencing alcohol‐related problems independent of an individual's level of alcohol consumption (Lipperman‐Kreda et al., ; Mair et al., ). For example, parties are the most commonly reported context for alcohol use among high school seniors (McCabe et al., ), and larger parties are associated with increased risk for drinking (Egan et al., ; Lipperman‐Kreda et al., ; Wagoner et al., ).…”
mentioning
confidence: 99%
“…Preliminary evidence indicates that adolescents differentially select drinking contexts. In an earlier analysis of the same sample of California youth (Lipperman‐Kreda et al., ), older, more frequent drinkers were more likely to drink at parties and someone else's home without parents. Deviant youths, defined as those who are involved in behaviors that are illegal, socially disapproved, and/or age inappropriate (Donovan et al., ; Jessor and Jessor, ; Jessor et al., ), were more likely to drink in almost all contexts, although the relationship of deviance to alcohol use in outdoor places (roughly 100% greater for every unit increase in deviance score) was much larger than for alcohol use in youths' homes (59%), at parties (22%), or someone else's home (19%).…”
mentioning
confidence: 93%